Fabrication and in vitro characterization of luffa-based composite scaffolds incorporated with gelatin, hydroxyapatite and psyllium husk for bone tissue engineering. Issue 17 (23rd November 2022) - Gundu, Shravanya; Sahi, Ajay Kumar; Varshney, Neelima; Varghese, Johny; K. Vishwakarma, Niraj; Mahto, Sanjeev Kumar
Abstract: Bone tissue engineering is an emerging technology that has been developed in recent years to address bone abnormalities by repairing, regenerating and replacing damaged/injured tissues. In present work, we report the fabrication and characterization of porous luffa-based composite scaffolds composed of Luffa cylindrica (sponge gourd) powder (LC)/hydroxyapatite (HA), psyllium husk (PH) and gelatin (G) in various combinations (w/v) i.e. 3% LC, 5% LC and control (C) (without luffa powder) by using freeze-drying method. The structural stability of the scaffolds was obtained after chemically crosslinking them with glutaraldehyde (GTA), which was identified via scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC). The hydrophilic behavior of the samples was quantified by water contact angle measurements. The average pore size of the scaffolds was observed in a range of 20–240 µm. As per the obtained data, the apparent and effective porosities were estimated as ∼57.08 ± 4.38%, ∼50.58 ± 4.09%, ∼59.45 ± 1.60% and 51.37 ± 3.36%, 47.94 ± 4.57% and 53.09 ± 5.45% for 3% LC, 5% LC and control (C) scaffolds, respectively. The scaffolds were found to be noticeably stable for 50 days at 37 °C in a lysozyme solution. The liquid retention capacity of the scaffolds revealed that the luffa-based scaffolds gained lower retention capacity compared to the control (C) scaffold; indicating an increase in scaffold stiffness due to the addition of luffa. Compressive strength study demonstrated that the mechanical stability of the fabricated luffa-based scaffolds got increased significantly from ∼1.5 to ∼9.5 MPa, which is comparable to that of trabecular bone. In addition, proliferation and viability analysis of MG-63 osteoblast-like cells revealed a significant level of cellular compatibility i.e. approaching ∼64% proliferation by 6th day in vitro compared to control. Thus, the obtained results demonstrate that the fabricated novel luffa-based scaffolds exhibit good cytocompatibility, remarkable porosity and excellent mechanical strength comparable to native human bone. Therefore, we anticipate that the developed luffa-based scaffolds could be a promising candidate for bone tissue engineering applications.